Health Equipment Maintenance Management at Arifin Achmad Regional General Hospital, Riau Province - Yulika, Della; Nasution, Mimin Sundari (CV. Rayyan Dwi Bharata, 2024)
Most medical equipment cannot function properly due to a lack of maintenance activities, including at Arifin Achmad Regional General Hospital. Scheduled maintenance activities are not carried out according to the established schedule, and unscheduled maintenance activities often experience delays, resulting in hospitals experiencing a shortage of medical equipment. This study aims to analyze the management of medical equipment maintenance at Arifin Achmad Regional General Hospital and the factors inhibiting maintenance management. The theory used is the maintenance management theory by Ignatius Deradjad Pranowo, which has 6 indicators: maintenance planning, maintenance scheduling, managing the execution of maintenance actions, evaluating maintenance performance, ensuring sustainable repairs, and possible equipment redesign. This study uses qualitative research with a descriptive nature. The results of the research found that the maintenance management of medical equipment at Arifin Achmad Hospital has not been fully implemented well, seen from the indicators of managing the implementation of maintenance actions and in allowing maintenance actions not to be carried out optimally. Inhibiting factors in Medical Equipment Maintenance Management at Arifin Achmad Hospital are slow administrative processes, lack of awareness of the importance of maintenance, large workload on technicians, dependence on third parties, and lack of evaluation of maintenance.